Antibiotics on incidence of infection in neonates with meconium-stained amniotic fluid - Kosim, M. Sholeh; Noerpramana, N. P.; Aminullah, Asril; Hadisaputro, Suharyo (Paediatrica Indonesiana, 2013)
Background The effectiveness of antibiotics for preventing infection in neonates with meconium-stained amniotic fluid (MSAF) remains unclear. Not all neonates with MSAF develop meconium aspiration syndrome (MAS) or neonatal infection. Furthermore, neonatal infection diagnosis may be difficult due to lack of symptoms. As such, clinical manifestations, laboratory results, and infection markers are important for diagnosis. Objective To evaluate antibiotic use on the incidence ofinfection in neonates with MSAF. Methods This double-blind randomized controlled clinical trial was performed at Dr. Kariadi Hospital, Semarang, Indonesia from October 2009 to March 2010. Subjects were newborns with MSAF who were diagnosed by two observers (Kappa test intraobserver agreement was 0.74) and with feces metabolites found in their amniotic fluid. Sixty-nine newborns were divided into groups I and II, comprised of 35 and 34 subjects, respectively. Group I subjects (control group) were not given antibiotics, while group II subjects (treatment group) were given combination antibiotics of ampicillin (50 mg;kg BW) and gentamicin (8 mg;kg BW), as single doses. Neonatal infection diagnosis was based on clinical manifestations, laboratory results (leucocyte count, blood culture, and I: T ratio), and the following infection markers: procalcitonin (PCT), interleukin-6 (IL-6), tumor necrosis tumor-a (TNF-a), and C-reactive protein (CRP). Chi-square and Fischer’s exact tests were used for statistical analyses. Results We found no significant differences in the incidence of neonatal infection between those who received and those who did not receive antibiotics, based on clinical manifestations, the first and second examination of laboratory marker (P=0.53), examinations of CRP, IL-6, TNF-a, and PCT either as single markers or combinations of 2, 3, or 4 markers (P> 0.05) , as well as mortality rate (P=0.30). Conclusion There is no significant difference in the incidence of infection in neonates with MSAF who received prophylactic antibiotics compared to those who did not receive antibiotics.